Unlocking resilience: exploring climate dynamics in small-scale irrigation systems of Sissala West District of north-western Ghana - Susan, Libanus; Kanlisi, Simon Kaba; Abdulai, Abdul-Razak Ahmed (Frontiers in Climate, 2025)
This study explores climate dynamics and resilience of small-scale irrigation facilities in the Sissala West District of north-western Ghana. A multiple cross-sectional case study design was used. We randomly and proportionately sampled 208 small-scale irrigation farmers for the study. We used questionnaire, Focus Group Discussions, and semi-structured interviews for data collection. The quantitative data were analysed using the Statistical Package for Social Sciences, while thematic analysis was applied in analysing the qualitative data. The findings indicate that rainfall variability and high temperatures pose serious threats to irrigation dams and dugouts, resulting in their inability to have enough water for dry-season farming. The irrigation farmers, therefore, experienced low yields, low income, and loss of investment. Variability of rainfall, high evapotranspiration, and scarcity of irrigation water were responsible for the under-utilisation of irrigation assets in the district. Planting of trees around reservoirs; addressing erosion using vetiva grass on the embankment of the dams and dugouts, regular maintenance of lateral canals, avoidance of farming very close to the basins and river beds to the dams can address siltation. The District Assembly needs to prioritise the rehabilitation and regular monitoring and supervision mechanisms in collaboration with the user communities to promote the achievement of long-term benefits of dry season farming.